Evaluation of modified essay questions (MEQs) as an assessment tool in third-year medical students’ modular summative assessment - Ayman Elsamanoudy; Mohamed Shehata; Amer Almarabheh; Zienab Alrefaie (BMC Medical Education)
Abstract Aim Whether case-based modified essay questions (MEQs) are crucial to summative assessment in medical curriculum is still debatable. The current study aimed to evaluate third-year medical students’ performance in case-based MEQs and multiple-choice questions (MCQs) in summative assessment in the endocrine module. Methods Students’ scores in mid and final module MEQs and MCQs were analyzed over four successive years from 2018/2019 to 2021/2022, where comparisons were made between students’ scores in MEQs and MCQs, and between scores of students of different categories. Moreover, the correlation between MEQs and MCQ scores and total grades was evaluated. Results The study revealed better students’ performance in MCQs compared to MEQs, and this pattern persisted over the study period reflecting that case-based MEQs were challenging to students. High-performing students got higher scores in MEQs than the low performers, denoting the ability of MEQs to discriminate between high and low grades. It was also observed that MEQs correlated significantly with students’ final grades similar to the MCQs indicating its importance as an assessment tool. Concerning the COVID year, students got higher grades in MCQs and lower scores in MEQs compared to other years of the study period which clarifies that MCQs offer a reliable assessment tool during exceptional circumstances. Conclusion Implementing case-based MEQs and MCQs in the summative assessment of medical curriculum favored discrimination between high and low scorers, minimized chances for students’ guessing and fostered deep learning and analytical comprehension of knowledge, and ensured medical students’ exposure to various item types. The current findings highlight the potential of using well constructed case-based MEQs in high stake medical exams together with MCQs for comprehensive assessments of problem solving skills.